Critical Remarks On the Implementation of the Anti-Tax Avoidance Directive in The Bulgarian Legislation (UNWE Yearbook, 2023)
The aim of the current paper is to outline some challenges regarding the implementation of the Anti-Tax Avoidance Directive (ATAD) in the Bulgarian legislation. For this purpose, specific aspects of the ATAD’s legal nature will also be examined in general. In this regard, the main applied methods used are the historical, the comparative and the logical.The author would like to draw attention to the relationship between the secondary European (EU) tax law and the relevant domestic provisions as key factors for the national tax policy regarding the tax avoidance from direct taxes’ perspective. The summary of the findings will help to estimate the efficiency of the new rules and the necessary steps for their further improvement. It will also outline the future trends on this issue.